Counterproductive Method of Hermeneutics as The Tafsir Al-Qur’an Studies - Ghozali, Mohammad (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2017)
Hermeneutics is the philosophy of interpretation that originated from the tradition of Bible interpretation. Among Muslim scholars, there is a mindset of interpreting the Qur’an that clearly adopts the hermeneutic method. Muslim scholars who support this adoption work believe that this method can bring changes to the method of Qur’anic interpretation, which they have long considered stagnant. The Qur’an, as a sacred scripture, is revered and used as a guide for life by Muslims. The Qur’an is the word of God, revealed to Prophet Muhammad (peace be upon him) through the Angel Gabriel for humanity in this world. The adoption of the hermeneutic theory is seen as the initiator of a new interpretation method. Hermeneutics, as an interpretation method, is highly counterproductive with the salaf al-salih scholars in understanding the message of the Qur’an, so that the subtlety of intelligence (accuracy of understanding) and the subtlety of explication (accuracy of explanation) of the verses of Allah can be traced comprehensively. Hermeneutika merupakan filsafat penafsiran yang lahir dari tradisi intepretasi Bible. Di kalangan cendekiawan Muslim terdapat mindset penafsiran Al-Qur’an yang tampak sekali mengadopsi metode hermeneutika. Cendekiawan Muslim yang mendukung kerjakerja adopsi ini yakin bahwa metode ini mampu membawa perubahan dalam metode penafsiran Al-Qur’an yang selama ini mereka anggap jumud. Al-Quran sebagai kitab suci yang disakralkan dan dijadikan pegangan hidup oleh umat Islam. Al-Quran adalah kalam Ilahi, diturunkan kepada Nabi Muhammad saw. melalui Malaikat Jibril bagi umat manusia di dunia ini. Pengadopsian terhadap teori hermeneutika itu dianggap pencetus metode tafsir baru. Hermeneutika sebagai sebuah metode interpretasi yang sangat kontraproduktif dengan para ulama salaf al-shalih dalam memahami pesan Al-Quran agar subtilitas intelegensi (ketepatan pemahaman) dan subtilitas ecsplicansi (ketepatan penjabaran) dari ayat-ayat Allah bisa ditelusuri secara komprehensif.